The search for biomarkers of immune restoration disease associated with Mycobacterium tuberculosis in HIV patients beginning antiretroviral therapy - Oliver, B.; Price, Patricia (2011)
Immune restoration disease associated with Mycobacterium tuberculosis is a complication of antiretroviral therapy seen in a subset of HIV-1 patients soon after they commence antiretroviral therapy. It is characterized by a 'paradoxical' worsening of treated tuberculosis or an 'unmasking' of subclinical tuberculosis. As antiretroviral therapy becomes increasingly available in countries with a high prevalence of tuberculosis, this form of immune restoration disease will become more common. Here we summarize biomarkers that may illuminate immunopathogenesis and assist in diagnosis. © 2011 Future Medicine Ltd.